(untitled) (Research, Society and Development, 2021)
Using biomaterials, he goes back to historical times and seeks to find a home for a better quality of life and an increase in life expectancy. Among the various materials applied as intuitively, the polymeric biomaterials stand out in the application of the treatment of holidays, especially due to their properties. A chitosan that stands out with its antimicrobial action, biodegradability and biodegradability and or polyvinylpyrrolidone (PVP) with its biocompatibility and its non-toxicity. However, in search of unique biomaterials with different responses, we raise the association of materials that we can promote changes of properties, such as thermals. During the exposition, this research investigates the thermal analysis of chitosan and PVP in its mixtures. For this, the polymers were characterized by thermogravimetric analysis (TGA) and differential exploratory calorimetry (DSC). Subsequently, it was simulated to degradation of the polymeric mixture, based on the results of the TGA of raw materials in a linear model and applied to the responsive surface methodology (MSR). From thermal analyzes by DSC, the transition temperatures of two polymers will be observed, and the TGA and its derivative are visualized in the presence of the density and degradation profile of raw materials, which corroborate with literature studies. Through the MSR, a degradation profile model was created at 350° C for mixing two polymers considering the linear model, where it was verified that, with mass concentration and proportion of polymers, we modify the degradation profile, using chitosan or higher factor influence.